PARENTAL RISK AVERSION AND INVESTMENT IN CHILDREN'S EDUCATION - Nurrachmat, Janaska; Sastiono, Prani (Fakultas Ekonomi dan Bisnis, Universitas Airlangga, 2022)
Introduction: The purpose of this study is to investigate the relationship between risk aversion and spending in children's education. Spending in children's education can be classified as an investment with uncertain outcomes and the return might yield in a relatively long time. It is predicted in this study that risk aversion will have negative impact on spending in children's education. Methods: This study uses IFLS data and two-period panel regression. Multiple time periods are applied to demonstrate time-varying risk aversion. Results: The results suggest that lower degree of parental risk aversion increases the spending on children's education, which confirms the theory. Conclusion and suggestion: The result showed that risk aversion significantly affects the spending on children's education. As a consequence, the government should provide clear information about how important an education is, especially a higher degree. Providing the information may drive the parent to not view education for children as a risky investment.